2019
DOI: 10.3892/etm.2019.7606
|View full text |Cite
|
Sign up to set email alerts
|

miR‑490‑3p functions as a tumor suppressor in glioma by inhibiting high‑mobility group AT‑hook 2 expression

Abstract: Glioma is one of the most common types of malignant cancer and the significance of microRNAs (miRNAs) in cancer therapy has been demonstrated. In the current study, miR-490-3p expression was significantly downregulated in glioma tissue and cell lines. Overexpression of miR-490-3p inhibited glioma cell proliferation and migration in vitro . In addition, the high-mobility group AT-hook 2 (HMGA2) was identified as a candidate target gene of miR-490-3p. The current study demonstrated that mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…For example, hsa-miR-338-3p found to be significantly downregulated in GBM, acted as a tumorsuppressing gene whose silencing can inhibit malignant biological behaviors of glioma cells, was an independent prognostic biomarker associated with poor prognosis in glioma patients; 28 hsa-miR-139-5p is lower in blood and brain tissues of GBM, was identified as a tumor suppressor by negatively targeting Notch1; 29 hsa-miR-490-3p expression was significantly downregulated in GBM, which can inhibit glioma cell proliferation and migration. 30 GO and KEGG pathway analysis offered insight into the possible roles of DE-miRNAs in the pathogenesis of GBM. We found that the IFN-gamma pathway was involved in the most significantly enriched terms shared by all sample types, indicates that DE-miRNAs in GBM may affect the activation of immune system and is a key factor affecting disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…For example, hsa-miR-338-3p found to be significantly downregulated in GBM, acted as a tumorsuppressing gene whose silencing can inhibit malignant biological behaviors of glioma cells, was an independent prognostic biomarker associated with poor prognosis in glioma patients; 28 hsa-miR-139-5p is lower in blood and brain tissues of GBM, was identified as a tumor suppressor by negatively targeting Notch1; 29 hsa-miR-490-3p expression was significantly downregulated in GBM, which can inhibit glioma cell proliferation and migration. 30 GO and KEGG pathway analysis offered insight into the possible roles of DE-miRNAs in the pathogenesis of GBM. We found that the IFN-gamma pathway was involved in the most significantly enriched terms shared by all sample types, indicates that DE-miRNAs in GBM may affect the activation of immune system and is a key factor affecting disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Igf2bp2 is a target of HMGA2 in different cell types [56,74,75]; it is an mRNA binding protein also involved in stem cell maintenance in glioblastoma [121], a neural tumor in which HMGA2 is reactivated [122][123][124][125]. Similar to Hmga2, Igf2bp2 is initially expressed at high levels in cortical NPCs in the early neurogenic phase, and then downregulated in late NPCs in the gliogenic phase.…”
Section: Hmga1 and Hmga2 In The Development Of The Cnsmentioning
confidence: 99%
“…The χ 2 test was used to identify the differences in clinicopathological characteristics between the two groups. The results demonstrated that miR-769-3p levels in the serum and glioma tissues were significantly associated with the World Health Organization (WHO) grade (P<0.01) (17) and Karnofsky performance score (KPS; P<0.05) (18). No similar results were observed for other clinicopathological parameters, including age, sex and tumor size (all P>0.05; Table I).…”
Section: Resultsmentioning
confidence: 99%